2021
DOI: 10.2118/205384-pa
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Controlling Factors of Pressure Wave Propagation Behavior Induced by Pulsating Hydraulic Fracturing

Abstract: Summary Pulsating hydraulic fracturing (PHF) is a promising fracturing technology for unconventional reservoirs because it could improve the hydraulic fracturing efficiency through inducing the fatigue failure of reservoir rocks. Understanding of the pressure wave propagation behavior in wellbores and fractures plays an important role in PHF optimization. In this paper, a transient flow model (TFM) was used to describe the physical process of pressure wave propagation induced by PHF, and this mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…It was concluded the abrupt pulse pressure could produce a better pressurization effect. Hou et al 33 used the transient flow model to describe the physical process of pressure wave propagation caused by pulse hydraulic fracturing. The effects of pulse frequency, injection mode, injection position, and friction are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded the abrupt pulse pressure could produce a better pressurization effect. Hou et al 33 used the transient flow model to describe the physical process of pressure wave propagation caused by pulse hydraulic fracturing. The effects of pulse frequency, injection mode, injection position, and friction are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the form of the bottom hole pressure is controlled by the wellhead injection form in pulse hydraulic fracturing . A pulse flow at the wellhead can generate a cyclic load with the CAIMS at the bottom of the well.…”
Section: Methodsmentioning
confidence: 99%
“…It is found that the form of the bottom hole pressure is controlled by the wellhead injection form in pulse hydraulic fracturing. 15 A pulse flow at the wellhead can generate a cyclic load with the CAIMS at the bottom of the well. By contrast, a cyclic load with the CACMS at the bottom of the well is induced by the pulse pressure at the wellhead.…”
Section: Experimental Schemesmentioning
confidence: 99%
See 2 more Smart Citations